Political Institutions and International Patterns of Agricultural Protection - Beghin, John C.; Kherallah, Mylene (The Review of Economics and Statistics, 1994)
This paper analyzes the influence of political systems and rights in patterns of agricultural protection across commodities, countries, and over time. Four political systems and a qualitative index of political rights account for differences in political institutions. The analysis incorporates the effects of development, of constraints on tax collection feasibility, and of comparative advantages and terms of trade. Pluralistic systems are associated with higher agricultural protection levels, although in a nonlinear fashion. Access to pluralism appears to be important, although further democratization partly dissipates protection. Copyright 1994 by MIT Press.